Вплив положення віконних блоків по товщині стіни на теплотехнічні характеристики вузла їх примикання - Пашинський, В. А.; Настоящий, В. А.; Джирма, С. О.; Плотніков, О. А.; Остапчук, А. С.; Pashynskyi, V.; Nastoyashchiy, V.; Dzhyrma, S.; Plotnikov, O.; Ostapchuk, A. (Global Science Center LP, 2017)
Однією з вагомих складових втрат тепла через огороджувальні конструкції будівель є вікна та вузли їх примикання до стін. Проведені дослідження дозволили визначити положення вікна в товщі стіни, яке забезпечує оптимальний тепловий режим вузла примикання вікна до стіни в заданих кліматичних умовах експлуатації. Результати дослідження можуть бути основою для створення загальної методики визначення оптимального положення вікон різних типів у зовнішніх стінах різних конструкцій, що експлуатуються в різних кліматичних умовах. Впровадження результатів зменшить втрати тепла в вузлах примикання вікон та забезпечить відсутність конденсації вологи в зоні цих вузлів. One of the significant components of heat loss through the enclosure structures of buildings is the windows and junction nodes to the walls. The conducted researches allowed to determine the position of the window in the thickness of the wall, which provides the optimal thermal mode of the node, that connects the window to the wall in the given climatic conditions of operation. The results of the research may be the foundation for creating a methodology for determining the optimal position of windows of different types in the outer walls of different designs, operated in different climatic conditions. Implementation of the results will reduce the heat losses in the in the nodes of windows to the outer walls and ensure the absence of condensation in the zone of these nodes.
The influence of the position of the window blocks by wall thickness on thermal characteristics of junction node
Keywords: енергоефективність; втрати тепла; цегляні стіни; вікна ПВХ; температурні поля; energy efficiency; heat loss; brick walls; PVC windows; temperature fields